2011
DOI: 10.1590/s0103-64402011000500009
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effect of photodynamic therapy on Aggregatibacter actinomycetemcomitans and Streptococcus sanguinis

Abstract: New periodontal disease treatments are needed to prevent infection progression. Photodynamic therapy (PDT) is one of the greatest pledges for this purpose. It involves the use of light of specific wavelength to activate a nontoxic photosensitizing agent in the presence of oxygen for eradication of target cells, and can be used for photokilling of microorganisms. This study evaluated in vitro the photodynamic effect of 0.01% toluidine blue-O (TBO) in combination with an AlGaInP diode laser light source on Aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 18 publications
3
19
0
7
Order By: Relevance
“…We also aimed to compare the efficacy of this method with the use of each component alone, and we found that simultaneous application of curcumin and LED laser inhibited the growth of A. actinomycetemcomitans more efficiently than using curcumin or LED laser individually. Another survey by Mattiello et al 22 assessed the effectiveness of 0.01% toluidine blue accompanied by diode laser of Aluminum Gallium Indium Phosphorus (AlGaInP), on A. actinomycetemcomitans. They also found a positive effect of PDT on this bacterium, which was compatible with our results.…”
Section: Discussionmentioning
confidence: 99%
“…We also aimed to compare the efficacy of this method with the use of each component alone, and we found that simultaneous application of curcumin and LED laser inhibited the growth of A. actinomycetemcomitans more efficiently than using curcumin or LED laser individually. Another survey by Mattiello et al 22 assessed the effectiveness of 0.01% toluidine blue accompanied by diode laser of Aluminum Gallium Indium Phosphorus (AlGaInP), on A. actinomycetemcomitans. They also found a positive effect of PDT on this bacterium, which was compatible with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Apresenta um baixo custo para sua produção e baixo risco para olhos desprotegidos. Ainda, está sendo empregado na TFA devido ao seu alto custo-benefício [20,21].…”
Section: Análise Da Efetividade Da Tfaunclassified
“…3 Light and drug are nontoxic by themselves; hence, only cells bound by PS and receiving light are affected by ''photodynamic action.'' 3 PACT treatments of bacteria including Streptococcus mutans, 4,5 Streptococcus sanguinis, 6 Porphyromonas gingivalis 7 and Actinobacillus actinomycetemcomitans 6 have shown positive outcomes. Toluidine blue has been shown to have bactericidal effects against gram-positive and gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%